THE IMPACT OF TEACHERS’ PROFESSIONAL TRAINING ON STUDENTS’ ACHIEVEMENT IN ENGLISH AS A FOREIGN LANGUAGE: A BENIN CASE - HINDEME, Ulrich Orlando Sèna; KOTTIN, Evariste; EGOUNLETI, Pédro Marius; KOUTCHADE, Blaise (My University, 2022)
This research work explores the impact of teacher professional development on the academic performance of EFL students. It examines the importance of the teacher education program and how it influences their teaching proficiency and the performance of their EFL learners. A qualitative research methodology was adopted for this study. Twenty (20) EFL teachers were the participants in this study, including five (05) teachers who have received professional training and fifteen (15) teachers who have not received professional training. The participants were purposively selected from three (3) public schools in two regions of Benin. Classroom observation and interviews were the instruments of data collection and the data gathered were analysed using a content analysis. The main findings of this study indicated that teacher training is important in influencing the quality of teaching and learning. Many Beninese EFL teachers do not have professional training, which contributes to the poor academic performance of students. This is because untrained teachers are inexperienced, while trained teachers use appropriate techniques to teach and understand the psychology of their learners. The availability of qualified teachers will result in better learning outcomes. In short, it was recommended that government and educational authorities organize in-service training programs for teachers to improve the quality of their teaching.
Keywords: teachers’ professional training; teaching competence; students’ academic; achievements; EFL